‘Masonic School’, ‘Secular School’: A Note on the Educational Policy of Latin Freemasonry in the Muslim Mediterranean, 19th - beginning of the 20th centuries - Zarcone, Thierry (2017)
Lodges founded by French, Italian and Spanish obediences in Eastern Mediterranean countries: Turkey, the Middle East and Magreb countries, started schools that were qualified as “masonic” “secular” o “Free secular”. These obediences were in conflict, in this regard ,with Christian congregations, with moslem ones, and , in some cases, with the synagogues. This paper  deals more specifically with some schools built  by the French and Italian obediences in the Ottoman Empire, at the turn of the 19th century confronting them with the schools in the Middle East and the Magreb belonging to these same obediences as well as by the Grande Oriente Español. It is important for us  to question the terms the freemasons used to refer to those schools. Whether it was common usage to present them, at the end of the 19th century,  as “secular schools”, instead of calling them “masonic schools”, which was generally their first  title/name, thus revealing that the educational Project should have  elements of masonic morality and of masonic ideals.